Socialization of Renewable Energy Utilization and Book Grants to Universiti Malaysia Perlis - Fadlan Siregar, Muhammad; Maizana, Dina; Satria, Habib; Dayana, Indri; Mungkin, Moranain; Hermansyah; Winda Sari, Vina; Tri Nugraha, Yoga; Jusoh, Muzzammil; Irwanto, Muhammad; Zakaria, Zulkarnay (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2024)
The use of renewable energy is increasingly important to meet energy needs and reduce the negative impacts of fossil fuel use. Universiti Malaysia Perlis (UniMAP) plays an active role in the socialization of renewable energy through educational programs and grants of related books aimed at increasing public understanding of the benefits of sustainable energy. Collaboration with Universitas Medan Area and Al-Azhar University will expand the reach of this socialization and enable the exchange of knowledge and experiences in the field of renewable energy. These books cover a variety of topics on renewable energy and green technology, and will be distributed in seminars and workshops involving academics and local communities from the three institutions. With this effort, it is hoped that awareness of the importance of the transition to clean energy will increase, encourage sustainable practices, and strengthen research in the field of renewable energy at UniMAP and partner institutions, making it a model for other institutions in promoting sustainable practices in the community.